2014
DOI: 10.5539/jedp.v4n2p65
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Related Symptoms in Swedish Adolescents: A Study in Two Upper Secondary Schools

Abstract: Aims: Psychiatric symptoms, sleeping problems and stress are increasing in Swedish adolescents. The aim of this study was to test the hypothesis that a combination of two potential stressors (i.e., high academic proficiency and high urbanicity) in a school setting would be related to increased stress levels and stress-related symptoms among pupils. Our second aim was to evaluate correlations between perceived stress and psychiatric symptoms, sleep quality and personality traits. Methods: 202 Swedish high-schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the process of choosing the population, we opted for two different schools in terms of academic performance and urbanicity, to obtain an adequate sample that could be considered relatively representative of Swedish upper secondary school students. This selection is more thoroughly described in the baseline cross-sectional study [ 11 ], which represents a larger randomised, controlled, single-blinded study (CHAMPS) aimed to investigate whether iMBI could be used to prevent psychiatric and stress-related symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the process of choosing the population, we opted for two different schools in terms of academic performance and urbanicity, to obtain an adequate sample that could be considered relatively representative of Swedish upper secondary school students. This selection is more thoroughly described in the baseline cross-sectional study [ 11 ], which represents a larger randomised, controlled, single-blinded study (CHAMPS) aimed to investigate whether iMBI could be used to prevent psychiatric and stress-related symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…We used three well-defined, well-validated, and reliable psychometric tests, before and after the intervention, that had previously been used on adolescents: the Symptoms Checklist 90 (SCL-90) [ 54 ], the Perceived Stress Scale (PSS-14) [ 55 ], and the Pittsburgh Sleep Quality Index (PSQI) [ 56 ]. The combination of scales was chosen to give an insight into the students’ perceived stress (PSS-14) and likely outcomes of that stress, expressed as low-quality sleep (PSQI) and increased general psychiatric symptoms (SCL-90), as previous studies have shown bi-directionally stress-associated impairments in psychiatric symptoms and sleep [ 11 ]. The time required to fill in the questionnaires was adjusted to avoid questionnaire fatigue and keep good test–retest reliability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, when selecting the study population, we opted for two schools that differed in terms of socioeconomic status, academic proficiency profile, urbanicity, and geographic location with the aim of obtaining a sample as representative as possible. This has been requested in previous studies (22,33,57).…”
Section: Limitations and Strengthsmentioning
confidence: 96%
“…Bergska skolan has 385 students and is the only upper secondary school in Finspång with national education programs. Finspång is a rural town (20,747 inhabitants in 2010) (Statistiska Centralbyrån, 2013) with heavy industry (Antonson, Thorsén, Sundquist, & Sundquist, 2014).…”
Section: Populationmentioning
confidence: 99%